The Role of Doctors in Facing the COVID-19 Pandemic in the Indonesian Worker Community - Linda Dewanti (Faculty of Medicine, Public Health, and Nursing, 2021)
COVID-19, which is caused by the SARS-CoV-2 virus, first entered and infectedIndonesians on March 1, 2020. A woman (31 years old) felt sick two days afterdancing with a Japanese citizen living in Malaysia, who was also recently confirmedto have COVID-19. The woman's mother (64 years old) was finally infected andconfirmed as a sufferer of COVID-19. Since then, among all contacts from Japanesecitizens (33 people consisting of drivers, guides, restaurant waiters, and other guestsat the dance) and from the first COVID-19 case in Indonesia (80 people), most peoplewere those who worked directly related to the case tracing 1 . A total of 11 people wereconfirmed to have an infection, with 2 of them were asymptomatic cases. Of the 11people, 10 were contacts of the foreign nationals; and 1 case was the first Indonesiancitizen's mother.The next COVID-19 cluster description in the community is very similar to the firstcluster, namely work-related contacts and family contacts. New clusters continue toemerge from various industries and offices that dominate the number of new cases inIndonesia.